Effect of Dwarf and Naked Neck Gene on the Egg Production Performance in Tropics (Progressive Agriculture, 2014)
Cocks and pullets from each of 4 genotypes; Redbro (RbRb), Naked neck (NaNa), Redbro dwarf (Rbdw) and Naked neck dwarf (Nadw) were crossed reciprocally for egg production trial. Egg quality (egg weight, egg diameter, egg length, shell thickness, membrane thickness, membrane weight, shell weight, % of shell, yolk color score, albumen diameter, albumen height, yolk diameter and yolk weight) were compared among 4 genotypes. Daily feed intakes, almost related to respected body size were reduced in Rbdw and Nadw hens by 7.41 and 19.89% than in normal sized RbRb hens. The feed conversion and hen day egg production were highest in Rbdw, intermediate in RbRb and Nadw and lowest in NaNa. Naked neck (Na) and dwarf genotypes had favorable effect on egg fertility and hatchability. Parents in both Na and dw inheritance had favorable shell thickness, shell membrane weight (%), albumen height and diameter, yolk height and diameter, albumen weight and albumen weight (%) and yolk weight, while NaNa had highest yolk weight (%). Both egg weight and chick weight percent were highest in RbRb x Rbdw genotypes, followed by RbRb, RbRb x Nadw, RbRb x NaNa, Rbdw x RbRb, Rbdw, Rbdw x Nadw, Rbdw x NaNa, Nadw x RbRb, Nadw x Rbdw, Nadw, Nadw x NaNa, NaNa x RbRb, NaNa x Rbdw, NaNa x Nadw and NaNa respectively. Chick weight as percent of egg weight irrespective of genotype was simply the functions of egg weight.DOI: http://dx.doi.org/10.3329/pa.v18i2.18167 Progress. Agric. 18(2): 115 - 121, 2007